High failure rates with a large-diameter hybrid metal-on-metal total hip replacement: clinical, radiological and retrieval analysis. - Bolland, B; Culliford, D; Langton, D; Millington, J; Arden, N; Latham, J (2011)
This study reports the mid-term results of a large-bearing hybrid metal-on-metal total hip replacement in 199 hips (185 patients) with a mean follow-up of 62 months (32 to 83). Two patients died of unrelated causes and 13 were lost to follow-up. In all, 17 hips (8.5%) have undergone revision, and a further 14 are awaiting surgery. All revisions were symptomatic. Of the revision cases, 14 hips showed evidence of adverse reactions to metal debris. The patients revised or awaiting revision had significantly higher whole blood cobalt ion levels (p = 0.001), but no significant difference in acetabular component size or position compared with the unrevised patients. Wear analysis (n = 5) showed increased wear at the trunnion-head interface, normal levels of wear at the articulating surfaces and evidence of corrosion on the surface of the stem. The cumulative survival rate, with revision for any reason, was 92.4% (95% confidence interval 87.4 to 95.4) at five years. Including those awaiting surgery, the revision rate would be 15.1% with a cumulative survival at five years of 89.6% (95% confidence interval 83.9 to 93.4). This hybrid metal-on-metal total hip replacement series has shown an unacceptably high rate of failure, with evidence of high wear at the trunnion-head interface and passive corrosion of the stem surface. This raises concerns about the use of large heads on conventional 12/14 tapers.